Mediation effects of positive and negative affect on the relationship between emotional intelligence and life satisfaction in rural school teachers - Deng, Xiaoxiang; Chen, Jiasheng; Zhao, Yuyang (Frontiers in Psychology, 2023)
Few studies have investigated the ways in which the specific facets of trait emotional intelligence (EI), positive affect (PA), and negative affect (NA) influence individuals’ general life satisfaction, especially in teachers. This study explored the effects of three facets of trait EI (appraisal and expression of emotions (AEE), utilization of emotion (UE), and regulation of emotions (RE)) and two typical affects (PA and NA) on teachers’ general life satisfaction. The participants were 577 Chinese rural school teachers (ages 18–49 years) who completed three questionnaires—the Schutte Self-Report Emotional Intelligence Test, Positive and Negative Affective scale, and Satisfaction with Life Scale. After validating the scales, a structural equation modeling analysis showed that trait EI, PA, and NA had a significant and positive effect on teachers’ general life satisfaction. PA played a partial mediating role between trait EI and life satisfaction. Furthermore, this study found that PA significantly and positively mediated the relationship between AEE, UE, RE, and life satisfaction. These results suggest that teachers with higher EI are more likely to have positive emotions, thereby enhancing their general life satisfaction, and that understanding the role of one’s own and others’ emotions and increasing positive emotions may be the key to improving teachers’ general life satisfaction. Future implications and the study limitations are discussed.